Dityrosine-Mediated Inhibition of α-Synuclein Fibrillation Using Photocatalytic Nanoparticles - Sonali Jena; Suman Jha (Proceedings)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the degeneration of dopaminergic neurons and the abnormal accumulation of alpha-synuclein (α-syn) aggregates or Lewy bodies in the substantial nigra of the brain [...]